On the rate of convergence of an unstable solution of a stochastic differential equation - Mynbaeva, G. U. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We study the rate of convergence of the process $ξ(tT)/\sqrt{T}$ to the process $w(t)/σ$ as $T → ∞$, where $ξ(t)$ is a solution of the stochastic differential equationd $ξ(t) = a(ξ(t))dt + σ(ξ(t))dw(t)$.